Development of an integrated model for environmentally and economically sustainable and smart cities - Azzam Abu-Rayash (22282462) (2024)
This research introduces a novel integrated approach for smart cities designed to enhance environmentally sustainable economies through innovations and socio-economic transitions. The model is uniquely and comprehensively developed to create a novel smart city index by integrating 32 performance indicators that notably transform the environment, economy, energy, social, governance and transportation dimensions. The present multidisciplinary conceptual model explores the intersection and cross-sectorial impacts in the quest to potentially achieve a smart city. The assessment methodology employs multi-criteria decision-making and principal component analysis to quantify results and visualize a helpful outcome. Geometric weighting schemes were also used to test the robustness of the model. The model is applied to 20 cities worldwide to determine the smart city index for each city. The smart city index is a composite index that considers smart health as a critical factor for humanity. The correlation between the society and economy indexes shows a significant positive exponential relationship. Enhancing the society index will result in potential economic growth for cities. The trend is supported by a relatively high degree of agreement. Other Information Published in: Sustainable Energy Technologies and Assessments License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.seta.2024.104096